PERANAN PAJAK UNTUK MENINGKATKAN KEMANDIRIAN ANGGARAN - Joko Waluyo (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2009)
The main subject of this paper are the role of tax revenue to central government budget and how reforms it to increase tax revenue. Financing budget deficits represent one of cause of state budget become annoyed. Ratio tax - PDB ranging from 13 – 15 percent showing good improvement, although still not yet optimal. Ratio tax – revenue and tax - expenditure progressively mount which indication that important taxation role progressively in budget revenue sources. In year of the research showing by change of tax structure from oil tax become the non oil tax, and also from indirect tax become to the direct taxes. Role of direct taxes progressively mount in taxation structure. Tax effort indicator and elasticity of tax revenue indicate that the good imposition efficiency progressively. To increase tax revenue without giving distortion to economics require to be conducted by a taxation reform.